Synthesizing structural and behavioral control for reconfigurations in component-based systems. (March 2016) - Khakpour, Narges; Arbab, Farhad; Rutten, Eric
Abstract Correctness of the behavior of an adaptive system during dynamic adaptation is an important challenge to realize correct adaptive systems. Dynamic adaptation refers to changes to both the functionality of the computational entities that comprise a composite system, as well as the structure of their interconnections, in response to variations in the environment, e.g., the load of requests on a server system. In this research, we view the problem of correct structural adaptation as a supervisory control problem and synthesize a reconfiguration controller that guides the behavior of a system during adaptation. The reconfiguration controller observes the system behavior during an adaptation and controls the system behavior by allowing/disallowing actions in a way to ensure that a given property is satisfied and a deadlock is avoided. The system during adaptation is modeled using a graph transition system and properties to be enforced are specified using a graph automaton. We adapt a classical theory of supervisory control for synthesizing a controller for controlling the behavior of a system modeled using graph transition systems. This theory is used to synthesize a controller that can impose both behavioral and structural constraints on the system during an adaptation. We apply a tool that we have implemented to support our approach on a case study involving https servers.